MEMAHAMI PERILAKU KONSUMEN UNTUK MEMENANGKAN PERSAINGAN BISNIS - Umar Chadhiq (AKSES: Jurnal Ekonomi dan Bisnis, 2007)
The goal of marketing is to meet and satisfy the need/expectation of consumers. While understanding consumers’ behavior is a must for producers to win the business competition. Consumers’ behavior will be affected by various factors, including psychology and socio-cultural. Companies are offering their products to meet the needs of customers to their satisfaction. And in the business world competitions are abound. In order to win the competition, a company must offer products that satisfy the customers. The achievement of a certain level of consumers’ satisfaction is one of the indications of winning a business competition, an achievement that must be maintained for the sustainable competitive advantage of a company.  Keywords: Consumers’ behavior, psychological and socio-cultural factors, consumers’ satisfaction, business competition